The Effect of Health Education on the Knowledge of Pregnant Women in the Handling of Emesis Gravidarum - Yenny Aulya; Jenny Anna Siauta; Siti Amnah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Emesis gravidarum is a natural thing and is often found in pregnancy, especially in the first trimester pregnancy usually occurs 6 weeks after the first day of the last menstrual period and lasts approximately 10 weeks due to an increase in the levels of estrogen and progesterone hormones produced by Human Chorionic Gonadotropin (HCG) in the serum from the placenta, but in cases it can continue until the second and third trimester of pregnancy. Objective to determine the influence of health education on the knowledge of pregnant women in the treatment of emesis gravidarum in the Working Area of the Batujaya Health Center, Karawang Regency. Quasi experimental research design one group pre-post test design. The sample in this study was 39 pregnant women in the first trimester who experienced emesis gravidarum. Technique of using Proportional Accidental Sampling. The questionnaire in this study has been tested for validity and reliability. Data analysis using descriptive statistics and paired t-test. Results: Showing the average value of knowledge before and after the intervention was 21.23 to 27.56. The results of the statistical test using the paired t-test obtained a value of p value = 0.000, meaning that there is an influence of health education on the knowledge of pregnant women in the treatment of emesis gravidarum. There is an effect of health education on the knowledge of pregnant women in the treatment of emesis gravidarum in the Working Area of the Batujaya Health Center, Karawang Regency.